Pulmonary tumour thrombotic microangiopathy presented as gastric signet ring cell carcinoma: A case report. Issue 3 (March 2020) - Cui, Ning; Wang, Lijun; Zhao, Jingming
Pulmonary tumour thrombotic microangiopathy (PTTM) is a rare complication of cancer characterized by widespread tumour cell emboli in small arteries and arterioles of the lung and often accompanied by microthrombi. We report a case of PTTM in a young Chinese woman that presented as gastric signet ring cell carcinoma. Although rare, PTTM should be considered in cancer patients with a rapidly progressing dyspnoea, chest computed tomography (CT) scan suggestive of pulmonary hypertension and diffuse pulmonary interstitial infiltration.